Sublime art : towards an aesthetics of the future - Zepke, Stephen (Crosscurrents (Edinburgh University Press), 2017)
Stephen Zepke shows how the idea of sublime art waxes and wanes in the work of Jean-François Lyotard, Gilles Deleuze and Felix Guattari, Jacques Derrida, Jacques Rancière and the recent Speculative Realism movement.